Science is not a Social Opinion - Marco Tatullo (Dentistry Journal, 2019)
Recently, the main American associations in the dental field reported concerns regarding a film on the Netflix, Amazon, Apple, and Vimeo platforms that reported that endodontic treatments of root canals are linked to serious systemic pathologies, against any scientific evidence. This extreme case highlights how information, in a social networking era, is dramatically conditioned by a small number of users, leading to large scale consequences in political opinions, alimentary choices, or even in healthcare policy. It is urgent to demonstrate a strong awareness by the academic, institutional, and associative bodies in order to restore the correct flow of information on mass media and social networks.